Correlation between dry land strength measurements and in water force generation - Carl, D. L.; Leslie, N; Dickerson, T; Griffin, B; Marksteiner, A (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: USA-Swimming supports the use of a specific dry land force measurement (Vasa Trainer) relative to in-water force generation. Imbalances between the measurements indicate the need to increase strength or enhance efficiency. The purpose of this study was to determine if two standard measurements of dry land strength would correlate with the ability to generate force in water as measured by a timed 22.9m swim or tethered swimming. METHODS: Subjects: N=25 (10 M, 16.6 y; 15 F, 16.3 y). Resistance Training: Bench Press - Subjects completed a barbell chest press with light weight for 10 repetitions. Following a 2 minute rest period, the weight was increased 10 % and another set of 10 repetitions completed. Subjects continued until they were unable to complete ten repetitions. 1RM was estimated using the following equation: Body weight/(1.0278-(.0278 x #reps)). Leg Press - Subjects completed a bilateral seated leg press following the same protocol as the BP. Swim Training: 22.9m Swim - Subjects completed two, 22.9m maximal swims from the starting block. Each swim was separated by 2 minutes. Times were recorded to the 100th of a second and averaged for best time. Tethered swim - Subjects completed two in-water tethered maximal swims (Digital Force Gauge, IMADA, Inc). Each trial was separated by1 minute. Force was recorded in N`s and the trials averaged for best effort. Statistics Analysis: Pearson Product Moment Correlation (R > 0.80). RESULTS: A significant correlation existed between BP strength and both the 22.9m swim and TeS for both sessions tested (R = -0.85 & -0.87; R = 0.82 & 0.80). A minor correlation existed between LP and 25 yard swim time (R = -0.70 & -0.77). No significant correlation existed between LP and TeS force generated. DISCUSSION: BP strength significantly correlated with both in-water force measurements. In addition, LP strength was significantly correlated with 25y swim time. Although LP was not correlated with TeS there was a significant difference when males were separated from females. For all measurements taken, males demonstrated a higher level of correlation. The differences observed between males and femalescould be due to the amount of muscle mass in males. Also, within this age range, males may have had more dry land weight training experience than females. In conclusion, BP strength may be an appropriate alternative to the Vasa Trainer as an indicator of discrepancy between strength and in water force generation.